Global innovational networks: Sense and role in development of global economy - Egor V. Dudukalov; Natalia D. Rodionova; Yana E. Sivakova; Elena Vyugova; Irina V. Cheryomushkina; Elena G. Popkova (Contemporary Economics, 2016)
The starting point for this research is the authors' hypothesis that global innovational networks play an important role in the development of the modern global economy because they stimulate international cooperation in the innovational sphere, the translation of knowledge in the global economic system, and general scientific and technological development and production development. The purpose of this article is to verify this hypothesis, conduct a complex study on the phenomenon of global innovational networks, and determine their purpose and role in the development of the modern global economy. The methodological basis of this research is founded on the logical modeling of economic systems and methods of structural and functional, systemic, and problem analysis. In the process of the research, the authors studied examples of global innovational networks created based on modern Europe that include countries from all over the world, namely, Horizon 2020, ERA.Net RUS, and Eurocores (European Collaboration Research). The authors also conducted complex analysis of statistical information on various global innovational networks, the dynamics of the quantity of innovational projects, realized participation in global innovational networks, and the significance of the global innovational indexes of countries of Western Europe (Great Britain, Germany, France, and Italy), Central and Eastern Europe (Czech Republic, Poland, Hungary, and Latvia) and Russia in 2005-2014. The authors provide a sense of global innovational networks, including their peculiarities and advantages; build a structural and logical model of the global market of innovations; and determine the role of global innovational networks in the development of the modern global economy.
Keywords: F63; O19; 330; global innovational networks; globalization; global economy; economic development